2020
DOI: 10.1016/j.breast.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of tumour marker velocity of cancer antigen 15–3 (CA 15–3) and carcinoembryonic antigen (CEA) in breast cancer surveillance

Abstract: Background Serum tumour markers, cancer antigen 15–3 (CA 15–3) and carcinoembryonic antigen (CEA) are not routinely recommended for detecting breast cancer recurrence and monitoring treatment. In this study, we aim to evaluate the diagnostic accuracy of absolute CA 15–3 and CEA levels and report on the clinical utility of tumour marker velocity in breast cancer surveillance. Methods 67 consecutive patients over a 15-year period (1998–2012) with available serial serum CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Tumour marker velocity may be a useful adjunct to absolute tumour marker values to distinguish between clinically significant elevated tumour markers from baseline variation. This suggests the clinical utility of serial CA 15-3 and CEA measurements in breast cancer surveillance [ 33 , 34 ]. Serum tumour markers such as CA 15-3 and CEA are still the most widely used serum tumour markers for surveillance purposes and treatment response in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Tumour marker velocity may be a useful adjunct to absolute tumour marker values to distinguish between clinically significant elevated tumour markers from baseline variation. This suggests the clinical utility of serial CA 15-3 and CEA measurements in breast cancer surveillance [ 33 , 34 ]. Serum tumour markers such as CA 15-3 and CEA are still the most widely used serum tumour markers for surveillance purposes and treatment response in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…A study on detection of breast cancer metastasis showed that combined detection of CA15-3 and CEA increased the sensitivity which proved that combined detection is more useful than single detection 32 . Again, it is reported that while CEA has a higher sensitivity of 75%, CA 15–3 has a higher specificity of 97%, the two tumor markers are complementary to each other, thus the combination of the two markers yielded a higher diagnostic accuracy 19 . However, it is worth noting that while the combined detection improves the sensitivity, the specificity decreases slightly.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that human breast cancer are characterized by a higher SF level, when compared with normal tissue 18 . However, these tumor markers for the detection of mammary gland tumor shows limited diagnostic sensitivity and specificity 14 , 19 . The detection of the combination of multiple specific tumor markers to improve the diagnosis of canine malignant mammary gland tumor specificity, sensitivity is of great importance in clinical diagnosis 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, circulating levels of CA 15–3/MUC1 in patients with newly diagnosed but unresected breast cancer were statistically significantly correlated with metabolic tumor volume and tumor lesion glucose on FDG-PET , providing evidence that CA 15–3 levels can reflect tumor burden ( 20 ). Additionally, in a case-control study that was nested in a cohort of patients who had undergone treatment for operable breast cancer, increases of more than 2.5 U/mL of CA 15–3 during 12 months were statistically significant predictors of recurrence ( P = .01) ( 21 ). This velocity is similar to the change of 1.18 U/mL during 6 months we observed (extrapolating to 2.36 U/mL during 12 months), and it suggests that even small changes in CA 15–3 during a short period of time have the potential to be clinically important.…”
Section: Discussionmentioning
confidence: 99%